2014
DOI: 10.1532/hsf98.2014402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lidocaine and Amiodarone on Prevention of Ventricular Fibrillation in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: We suggest that during coronary arterial bypass surgery, administration of an amiodarone regime before release of the aortic cross clamp, paying particular attention to the start of the initial effect of amiodarone, is no more effective than lidocaine for prevention from arrhythmia; however, amiodarone reduces the need for electrical defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…All included studies were RCTs and, according to the item standard quality evaluation, five were classified as high-quality and the other three as moderate quality studies (Table 1). Among these studies, four were three-arm trials (Ayoub et al, 2009;Mauermann et al, 2012;Ghavidel et al, 2013;Yilmaz et al, 2014) of amiodarone versus lidocaine versus placebo, three compared lidocaine with placebo (Kirlangitis et al, 1990;Baraka et al, 2000;Vaziri et al, 2010), and one compared amiodarone with placebo (Samantaray et al, 2010). In all studies, all patients were scheduled to undergo elective surgery and were age-, gender-, and operative condition-matched (Table 2).…”
Section: Quality Assessment and Characteristics Of Included Studiesmentioning
confidence: 99%
“…All included studies were RCTs and, according to the item standard quality evaluation, five were classified as high-quality and the other three as moderate quality studies (Table 1). Among these studies, four were three-arm trials (Ayoub et al, 2009;Mauermann et al, 2012;Ghavidel et al, 2013;Yilmaz et al, 2014) of amiodarone versus lidocaine versus placebo, three compared lidocaine with placebo (Kirlangitis et al, 1990;Baraka et al, 2000;Vaziri et al, 2010), and one compared amiodarone with placebo (Samantaray et al, 2010). In all studies, all patients were scheduled to undergo elective surgery and were age-, gender-, and operative condition-matched (Table 2).…”
Section: Quality Assessment and Characteristics Of Included Studiesmentioning
confidence: 99%
“…A comparative study of amiodarone administration with placebo before ACC release was shown to significantly reduce RVF occurrence in patients undergoing cardiac surgery (5,9), but other studies have reported contradictory results (10,11,14,15). Comparisons between amiodarone and lidocaine have also Abbreviations: ACC, aortic cross-clamp; AF, atrial fibrillation; AV, atrioventricular; CABG, coronary artery bypass surgery; CHD, coronary heart disease; CI, confidence intervals; CPB, cardiopulmonary bypass; CPR, cardiopulmonary resuscitation; CVD, cardiovascular disease; DCSs, defibrillation counter shocks; ED, endothelial dysfunction; IHCA, in-hospital sudden cardiac arrest; IRI, ischemia-reperfusion injury; ITT, intention-to-treat; IV, intravenous injection; LVEF, left ventricular ejection fraction; NO, nitric oxide; PRISMA, preferred reporting items for systematic reviews and Meta-analyses; RCT, randomized controlled trial; RVF, reperfusion ventricular fibrillation; RR, risk ratio; TLR-9, Toll-like receptor 9; VF, ventricular fibrillation; VHD, valvular heart disease; VT, ventricular tachycardia; VW, Vaughan-Williams.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients undergoing valve replacement surgery or coronary artery bypass surgery (CABG) are prone to risks associated with surgical complications such as arrhythmias, major bleeding, severe infection, and cerebral infarction (4). Ventricular fibrillation (VF) frequently occurs after aortic cross-clamp (ACC) release in patients undergoing open-heart surgery (5)(6)(7), which can result in reperfusion ventricular fibrillation (RVF) when myocardium reperfusion is initiated. This surgical consequence is associated with a negative impact on morbidity and mortality (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Previous studies have shown the effectiveness of amiodarone in preventing ventricular fibrillation following aortic cross-clamp release, but none have focused specifically on patients with left ventricular hypertrophy. [6][7][8] Left ventricular hypertrophy and contemporary aortic valve replacement techniques have been associated with poor myocardial protection, and place patients at risk for sustained ventricular fibrillation after crossclamp removal. 1 Moreover, the standard practice of administering amiodarone immediately after aortic cross-clamp release has been associated with suboptimal intramyocardial amiodarone concentrations, and may not prevent ischemiareperfusion injury-mediated ventricular fibrillation in this high-risk population.…”
mentioning
confidence: 99%